Analisis Peran Dinas Psikologi Tni Angkatan Laut Guna Menumbuhkan Perilaku Cinta Laut Masyarakat Pesisir - Sariwati, Dinari; Komaruddin, Komaruddin; Setiawan, Agung (Syntax Corporation, 2025)
This study aims to analyze the role of the Indonesian Navy’s Psychological Service (Dispsial) in fostering marine-loving behavior among coastal communities. The analysis is based on Soekanto’s role theory framework, which encompasses aspects of position, rights and obligations, as well as duties and responsibilities. A descriptive qualitative approach was employed, with data collected through in-depth interviews involving six key informants, including Indonesian Navy officials, academics, and local community leaders. The data were analyzed using NVivo 12 Plus software to identify themes and patterns of inter-informant connections. The findings reveal that Dispsial holds a strategic position within the Indonesian Navy's organizational structure, enabling it to actively engage in psychological development programs targeting coastal communities. Dispsial possesses the authority to determine intervention sites and is responsible for providing psychological support through psychoeducation, training, and research. This role is manifested through programs that effectively raise public awareness and emotional attachment to the sea. The study contributes theoretically to the development of maritime psychology and offers practical implications for strengthening collaboration between the military, academic institutions, and communities in shaping sustainable marine-oriented behavior..